Optimalisasi Manajemen Sumber Daya Manusia Pada Pegawai Negeri Sipil: Praktik Terbaik Dan Tantangan - Suartini, Ni Kadek (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Civil Servants (PNS) staffing management is a crucial aspect in carrying out effective government functions. In this context, challenges such as hiring that is less transparent, performance appraisal that is less objective, unequal opportunities for career development, and ineffective work discipline have become issues that require serious attention. The purpose of this research is to identify practical and strategic solutions to optimize civil servant personnel management in facing these challenges. The research method involves an in-depth analysis of the problems and the existing context, as well as formulating appropriate steps to overcome them. The results of this study underscore the importance of transparency in recruitment, emphasizing the establishment of clear and inclusive mechanisms. In addition, it is necessary to strengthen a performance appraisal system that is more objective, through the use of performance indicators that are measurable and closely related to the duties and responsibilities of civil servants. Efforts to ensure equal opportunities for career development are essential, including the provision of relevant training and development. Effective work discipline must also be strengthened, supported by real policies and actions to deal with indiscipline. The conclusion of this study emphasizes the need to implement these solutions in order to create a more adaptive and efficient civil servant management. It requires strong support from appropriate regulations, effective outreach, and the utilization of information and communication technology to improve the quality of personnel management. Collaboration between the government, civil servant organizations and the community is also an important factor in realizing positive change. Thus, this research hopes to provide guidance for improving civil servant personnel management, which will ultimately support the progress of governance and public services holistically.